Новый вид златоглазки (Neuroptera, Chrysopidae) из Таджикистана - Захаренко, А.В. (Вестник зоологии, 1983)
Nineta pomacea sp. n. (Tadjik SSR, Pamir Mts) — similar to N. impunciata Reuter, differs by almost green venation, shorter tip of the 9th sternite, not projecting over 10th tergite, and by pseudopenis shape.